Bioreactors for succinic acid production processes. (19th May 2019) - Ferone, Mariateresa; Raganati, Francesca; Olivieri, Giuseppe; Marzocchella, Antonio
Abstract: Succinic acid (SA) has been recognized as one of the most important bio-based building block chemicals due to its numerous potential applications. Fermentation SA production from renewable carbohydrate feedstocks can have the economic and sustainability potential to replace petroleum-based production in the future, not only for existing markets, but also for new larger volume markets. Design and operation of bio-reactors play a key role. During the last 20 years, many different fermentation strategies for SA production have been described in literature, including utilization of immobilized biocatalysts, integrated fermentation and separation systems and batch, fed-batch, and continuous operation modes. This review is an overview of different fermentation process design developed over the past decade and provides a perspective on remaining challenges for an economically feasible succinate production processes. The analysis stresses the idea of improving the efficiency of the fermentation stage by improving bioreactor design and by increasing bioreactor performance.